The Effect Role Playing Model: Development of Social Awareness and Relational Skills of Lower Grade Elementary - Hapsari, Rizqa Qodriannisa; Wulandari, Murfiah Dewi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of this study is to determine the influence of the role playing learning model on the development of social awareness and skills of lower grade elementary school students. Methodology: This study uses a quantitative research method with the type of experimental research. Data collection uses a questionnaire in the form of a Likert scale assessment. Results: The test results showed the influence of the role playing learning model on the development of social awareness and relational skills of elementary school students in lower grades. Applications/Originality/Value: The application of the role playing learning model has a significant effect on the development of social awareness and relational skills of elementary school students in lower grades. Through role playing activities, students get the opportunity to be actively involved in social situation simulations, so that they can improve their understanding of social norms, empathy, and the ability to interact with others.